Flotation therapy for downer cows - Metre D.C. Van; Jean G. St.; J. Vestweber (Kansas Agricultural Experiment Station Research Reports, 1996)
Cattle that become recumbent (unable to get up) as the result of calving difficulty, low blood calcium, traumatic injuries, or other disorders are prone to develop subsequent pressure damage of muscles, nerves, and areas of skin. The resulting medical problems that are secondary to prolonged recumbency may be more life-threatening than the initial medical disorder that caused recumbency. Flotation therapy is an effective means of physical therapy for rehabilitation of "downer" cattle. A description of flotation therapy and data from the first year of use of the flotation tank at the Veterinary Medical Teaching Hospital, Kansas State University, are presented.; Dairy Day, 1996, Kansas State University, Manhattan, KS, 1996;
Keywords: Dairy Day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-115-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 771; Downer cow; Recumbency; Flotation; Physical Therapy